Autofish Monitoring System - Mulchandani, M; Marshettiwar, D; Varma, R (International Journal of Computer Sciences and Engineering, 2025)
The proposed work is a system for automatic control of fish farming using sensors. Aqua-culture, also called as aqua farming, is the farming of aquatic organisms like fish, crustaceans and crabs and many other acquatic organisms by using the various sensors to detect the condition of the aquatic environment and reduce the the risks by detection. The proposed system assists remote monitoring of the fish farming system based on Internet of Things (IOT) for real-time monitor and control of a fish farming environment. The main objective of this manuscript is to provide an automatic monitoring system that helps us in saving time, money & power of the farmers. IOT technologies have revolutionized farm production in the country recently. In this fish farming process we use different sensors like pH value, temperature and water level sensors. By using these sensors we automate the work and it will also be easy to monitor the fish farming remotely from other location.